Lymphocytes and immunoglobulins in peripheral blood and lymphatic fluid of neonates with chylothorax - De Rose, Domenico Umberto; Landolfo, Francesca; Pugnaloni, Flaminia; Gassabi, Fatima Zahra; Martini, Ludovica; Santisi, Alessandra; Columbo, Claudia; Giliberti, Paola; Gazzotti, Fabia; Porzio, Ottavia; Capponi, Claudia; Perno, Carlo Federico; et al. (Frontiers in Immunology, 2025)
BackgroundNeonatal chylothorax is associated with high morbidity and mortality, partly due to increased infection risk from lymphocyte depletion and hypogammaglobulinemia. However, data specific to chylothorax cohorts are limited. This study aimed to investigate lymphocyte subsets and immunoglobulin levels in neonates with congenital and acquired chylothorax.MethodsWe retrospectively enrolled 18 neonates with chylothorax admitted to our NICU between January 2023 and January 2025. Inclusion criteria were term or preterm infants with congenital or acquired chylothorax and paired peripheral blood and chyle samples collected within 48 hours of effusion onset. Lymphocyte subsets and immunoglobulin levels were compared between blood and chyle, and between congenital and acquired chylothorax.ResultsChyle samples showed significantly higher leukocyte, lymphocyte (percentage and absolute), and T-cell counts compared to blood. Conversely, B lymphocyte percentages and Natural killer (NK) cell counts were significantly lower in chyle, as were IgG and IgM levels. Three patients (16.7%) had absolute lymphopenia, particularly within the T-cell and NK-cell subsets, and five (27.8%) had hypogammaglobulinemia. Fifteen infants (83.3%) developed late-onset sepsis, primarily bacterial, with some fungal cases. Absolute T-cell subset numbers in chyle were higher in acquired versus congenital chylothorax, while percentages and immunoglobulin levels were largely similar.ConclusionOur findings confirm a specific pattern of immune dysregulation in neonates with chylothorax, with distinct lymphocyte and immunoglobulin profiles in chyle. In particular, the T-cell subsets were enriched in the chyle. A multicenter, prospective randomized trial is warranted to assess the utility of immunoglobulin therapy in infection prevention in this population.